Implementasi Dalam Sistem Informasi Pada Analisis Beban Kerja Pegawai Yang Berbasis Website Di Surabaya - Marcellina Samudra; Muhammad Roisul Basyar (Jurnal Sistem Informasi dan Ilmu Komputer, 2024)
Workload often causes problems faced by employees in various agencies. Employee performance becomes ineffective and inefficient because the workload is too low or too high. The aim of this research is to conduct an analysis of the fatigue and workload of employees in the E-Government Administration Department. Analyzing workload is an important part of efforts to improve bureaucratic reform in government. The application of workload analysis helps determine the number of working hours required to complete a task, or in other words calculate the amount of work, responsibility or workload that must be borne by a person. Less than optimal application of workload analysis can affect employee performance, such as uneven distribution of employees, accumulation of employees in one unit, or an unbalanced number of employees. Therefore, a workload analysis application is needed to help manage job workload.